Comparison of American and Russian Colonization in Two Japanese Animation Film Isao Takahata's Hotaru no Haka and Shigemichi Sugita's Jopanni no Shima - Priventa, Hendrike; Handayani, Umi; Riani, Rosalina Wahyu (Program Studi Sastra Jepang, Universitas Jenderal Soedirman, 2023)
Animated films are part of literary works with a form of postmodern fiction. It is shown that animated films fulfill the requirements as literary works, which are fictitious, medium in language, and aesthetic. As a literary work, animated films have similar structures, such as characters, characterizations, settings, and plot. The purpose of this study is to compare the traces of American and Russian colonialism in both animated films by looking at their elements such as hybridity and mimicry. The research method that will be used in this research is descriptive qualitative. Descriptive research is research that aims to provide (describe) a condition or phenomenon that exists as it is. The shift in the meaning of